Megavoltage Radiotherapy for the Treatment of Degenerative Joint Disease in Dogs: Results of a Preliminary Experience in an Italian Radiotherapy Centre - Rossi, Federica; Cancedda, Simona; Leone, Vito Ferdinando; Rohrer Bley, Carla; Laganga, Paola (Frontiers in Veterinary Science, 2018)
The aim of the study was to evaluate the efficacy and toxicity of a low-dose radiotherapy treatment in dogs with osteoarthritis. Inclusion criteria were dogs affected by osteoarthritis of one or multiple joints, with lameness, previously treated with medical therapy and referred for radiotherapy because of chronic unresponsive pain. After suspension of medical therapy, dogs underwent external beam radiotherapy treatments delivered in three fractions of 2 Gy each. Medical records were reviewed and follow-up information was collected by clinical re-check and owners interview. Twenty-five dogs matched the inclusion criteria; among them, twenty-one had one course of RT and four underwent multiple treatments, respectively 218, 266, 39 and 1384 days after the first treatment. Clinical improvement was observed in 92% of patients with median benefit duration of 356 days after the first treatment, and 418 days after the second treatment. No side effects were recorded. In this group of patients, radiotherapy was effective, well tolerated and repeatable, leading to an improvement of quality of life in dogs with degenerative joint disease unresponsive to medical treatments.